2020
DOI: 10.33002/nr2581.6853.03047
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Environmental Knowledge of Borana Pastoralists

Abstract: This paper investigated the indigenous environmental knowledge (IEK) of Borana pastoralists in Dhas district of Borana zone in Southern Ethiopia. To select participants for key informant interview and focus group discussion (FGD), snowball sampling was used to pinpoint people who have IEK of Borana pastoralists. Results show that the customary practices of Borana pastoralists that linked to multi-dimensional natural resources management (NRM) include the taxonomy of pastureland and water resources instituted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In Gomole district, numerous generations of top-down development interventions purposely evaded indigenous knowledge on the grounds that modern models were superlative. Alemayehu and Doda (2020) indicated that development interventions such as adaptation to climate changes, conservation of natural resources and others, have variant implications for local knowledge. As a result, any plan to improve the quality of life of the local people will be vain if it doesn't confess the knowledge of the local communities.…”
Section: Challenges Faced By Indigenous Weather Forecasting Knowledge...mentioning
confidence: 99%
“…In Gomole district, numerous generations of top-down development interventions purposely evaded indigenous knowledge on the grounds that modern models were superlative. Alemayehu and Doda (2020) indicated that development interventions such as adaptation to climate changes, conservation of natural resources and others, have variant implications for local knowledge. As a result, any plan to improve the quality of life of the local people will be vain if it doesn't confess the knowledge of the local communities.…”
Section: Challenges Faced By Indigenous Weather Forecasting Knowledge...mentioning
confidence: 99%